2020
DOI: 10.15835/buasvmcn-asb:0002.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cumin Seeds (Cuminum cyminum) in Feed Diets of Anatolian Water Buffaloes on Shelter into Gass Concentration, Milk Yield and Composition

Abstract: The research was carried out to determine the effects of cumin seeds in food diets of Anatolian water buffaloes (AWB) in shelter about gas concentration, milk yield and composition. The animal material of the experiment was conducted with 27 buffaloes at Karaoglan Village located in Mustafakemalpasa, Bursa. Three different buffalo shelters (E1, E2 and E3) and three different diets (S1; S2; and S3) (0, 10 and 30 g grounding cumin seeds (GCS) kg-1) in 3x3 a replicated Latin square design was used with nine repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…GCS application significantly increasedto a total DM consumption (P < 0.01; 11.69,12.14 and 13.01 kg day −1 for S1, S2 and S3 diets, respectively). The total DM consumption washigher in buffaloes fed by S3 diet than in buffaloesfed by the S2 and S1 diets (6.68% and 10.14%, P < 0.01) (Table 3) [30]. In another study, Kirar et al [32] 12 lactating Murrah buffaloes of 1st to3 parity were randomly selected and distributed into two different groups with six animals in each group.…”
Section: Concentrate Feed Mixture (Cfm)mentioning
confidence: 99%
See 2 more Smart Citations
“…GCS application significantly increasedto a total DM consumption (P < 0.01; 11.69,12.14 and 13.01 kg day −1 for S1, S2 and S3 diets, respectively). The total DM consumption washigher in buffaloes fed by S3 diet than in buffaloesfed by the S2 and S1 diets (6.68% and 10.14%, P < 0.01) (Table 3) [30]. In another study, Kirar et al [32] 12 lactating Murrah buffaloes of 1st to3 parity were randomly selected and distributed into two different groups with six animals in each group.…”
Section: Concentrate Feed Mixture (Cfm)mentioning
confidence: 99%
“…In another study, Değirmencioğlu et al [30] A total of 27 multifarious AWB at stage 40-50 days of lactation were randomly selected and distributed into three different groups with 9 animals in each group. Animals in Group I fed by control ration, in Group II fed by control ration plus cumin seeds (GCS) 10 g kg −1 and in Group III fed by control ration plus 30 g GCS kg −1 .…”
Section: Concentrate Feed Mixture (Cfm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cumin seed is the hub of numerous bioactive compounds such as cuminaldehyde, alkaloids, flavonoids and terpenoids, which have various pharmacological properties such as antimicrobial, galactagogue, antioxidant, appetite enhancer and digestive stimulant (Singh et al 2021). Previous studies reported positive effects of cumin seed supplementation on milk production in ruminants (Miri et al 2013, Ghafari et al 2015, Morsy et al 2018, Değirmencioğlu et al 2020. However, no study has been conducted in India to assess the effect of feeding cumin seed in lactating goats.…”
mentioning
confidence: 99%
“…A research was carried out by Değirmencioğlu et al (2020) to determine the effects of cumin seeds in food diets of Anatolian water buffaloes (AW B) in shelter about gas concentration, milk yield and composition. It has been determined that 30 g cumin supplementation added to the early lactating AWB diets significantly increased total dry matter intake and milk yield of AW B (P<0.01).…”
mentioning
confidence: 99%